Analysis of the Influence of Service Quality and Company Image on Customer Trust in PT Jasa Raharja Representative Medan - Nelsi Agustina Siburian; Nurbaiti Nurbaiti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Financial institutions in Indonesia in various sectors have also experienced quite rapid development, one of which is in the insurance sector. Currently insurance companies in Indonesia are quite developed, this condition is shown by increasing public interest in using insurance products. This study aims to analyze the effect of service quality and corporate image on customer trust in PT Jasa Raharja Representatives of Medan. The population of this study was all customers of PT Jasa Raharja, with a total sample of 100 respondents. The sampling technique used is purposive sampling. The analysis technique used is multiple linear regression analysis using SPSS software. The results of the study show that service quality has a positive and significant effect on customer trust. Corporate image has a positive and significant effect on customer trust. As well as service quality and corporate image simultaneously have a positive and significant effect on customer trust.